The use of tracers in making accurate discharge measurement in pipelines - Filmer, Robert W., author; Yevjevich, Vujica M., 1913-, author; Engineering Research Center, Colorado State University, publisher (Colorado State University. Libraries, 1966)
The purpose of this investigation was to provide some field data for the diffusion of a soluble tracer (Rhodamine W-T) in pipes. Nine parameters were selected and their effect on tracer concentration distribution was studied. The most important parameters varied were: water discharge through the pipe, mixing distance and the injection probe geometry. The experiments were conducted in a 36-inch pipe line where it was possible to vary the rate of flow and mixing distance. Uniformity of the rate of dye injection was insured by the use of a Chemcon Model 1110 chemical proportioning pump which could be manually adjusted while a radial arm, some distance downstream from the injection point, could sample the solution at different positions in a cross-section. A Turner model 111 fluorometer constituted the detection device which combined the advantages of high sensitivity in dye detection, ruggedness and nearly complete independence from the power supply voltage. The degree of uniformity of mixing of the soluble tracer is represented by Cv, which is the coefficient of variation of the tracer concentration distribution. Values of Cv, calculated from the observed concentration data for each flow rate, were fitted by the function Cv = Ke^(αz) by the method of least squares, where z is the mixing distance and K and α are constants.
CER66RWF-VMY38.
October 1966.
Prepared under U.S. Bureau of Reclamation contract.
Keywords: Fluid dynamics; Hydraulic measurements; Pipelines